MODEL PEMBERDAYAAN DISABILITAS FISIK MELALUI PROGRAM ATENSI DI SENTRA BUDI PERKASA - Uci Adinda; Siti Badi’ah; Faisal Adnan Reza; Fatonah Zakie (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study aims to analyze the empowerment model of people with physical disabilities through the ATENSI (Social Rehabilitation Assistance) Program at the Budi Perkasa Center in Palembang. The research uses a descriptive qualitative approach with Talcott Parsons' functional structural theory through the AGIL (Adaptation, Goal Attainment, Integration, and Latency) scheme. Data were collected through participatory observation, in-depth interviews, and documentation of nine informants who were purposively selected from 86 beneficiaries. The results of the study show that the ATENSI Program implements holistic empowerment through vocational training, mental-spiritual guidance, fulfillment of decent living needs (ADL), and entrepreneurial assistance in the form of productive tools. This program increases the independence of beneficiaries in the aspects of community survival skills, personal care skills, home management skills, and work-related skills. AGIL's analysis shows the function of adaptation through training and tool assistance, goal achievement through increased independence, integration through service coordination, and pattern maintenance through spiritual coaching. The main challenge lies in the suitability of skills to the needs of the job market. This research contributes to the development of a model for empowering persons with disabilities that is holistic, sustainable, and more responsive to social policies and the demands of the world of work.